Corrective procedures remove relative age effect from world-class junior sprinters - Brustio, P. R.; Boccia, G. (Journal of Sports Sciences, 2021)
This retrospective study investigated whether corrective adjustment procedures can remove the relative age effect (RAE) from world-class junior sprinters at the beginning of their career. A total of 2,918 male and 3,029 female athletes competing in sprint races (100 m, 200 m, and 400 m) of the World Athletics lists between 2000 and 2018 were considered. Longitudinal quadratic trendline equations across ages 16-25 yrs were calculated considering athletes` exact age and respective performance. Corrective adjustment calculations from the estimated longitudinal quadratic equations were applied at 16 yrs and 17 yrs. RAE was investigated for the whole sample and top-level athletes (i.e., first Top50 and Top100) considering the uncorrected and corrected performance. Moderate to large RAE was observed in Top50 and Top100 at 16 yrs. Differently, a lower RAE was observed at 17 yrs. When re-examining the data using the corrective adjustment calculations, the RAE disappeared in all sprint events and both genders at 16 yrs, while a more equal distribution was observed at 17 yrs. Corrective adjustment procedures can remove or at least reduce the RAE in world-class sprinters. Applying simple equations based on exact age might improve the accuracy of performance evaluation and talent identification in international track and field sprint competitions.